Magnetic Resonance Imaging in Food Science - Hills, Brian (John Wiley & Sons, 2011)
This book presents a unified approach to food imaging by considering how MRI studies of foods undergoing processes such as drying, freezing, baking, extrusion, and freeze-drying can be modeled using mass and heat transport equations and how these mathematical models can be used in process design optimization programs